Representasi Emosi Tokoh Utama dalam Novel “Dia Angkasa” Karya Nurwina Sari Ke Web Series : Kajian Psikoanalisis - Lilik Rohmatin; Ari Nugrahani; Kingkin Puput Kinanti (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
The purpose of this study is to analyze the representation of the emotions of the main character in the novel Dia Angkasa by Nurwina Sari and its adaptation in the form of a web series, using a psychoanalytic approach according to Sigmund Freud. This research focuses on the question of how the emotions of the character Angkasa Naufal Merapi are represented in both media, and identifies the psychological conflicts that are the basis for character formation through the structure of id, ego, and superego. The qualitative descriptive method was used in this study with content analysis techniques, data sources from the text of the novel Dia Angkasa and its broadcast. Data collection techniques are carried out through intensive reading, recording, and coding of the categories of emotions produced in the form of anger, fear, love, and hope. Furthermore, the data was analyzed using psychoanalytic theory to understand the psychological dynamics of the characters. The results show that the emotions of the main characters in the novel are shown in depth through narrative and internal dialogue, while in the web series emotions are expressed more through visual and audio elements. There are differences in the depth of representation, but they complement each other in forming a complete understanding of the character. Psychoanalytic analysis shows that there is a conflict between instinctive impulses (id), consideration of reality (ego), and moral values (superego) in the main character, which shapes the emotional journey and maturity of the character.